ASSESSMENT OF SOCIO-PSYCHOLOGICAL HEALTH AS A FACTOR IN INCREASING MOTIVATION IN THE STUDY OF STUDENTS (ON THE EXAMPLE OF LEARNING A FOREIGN LANGUAGE) - Кошербаева, Айгерим; Канаева, Акмарал; Калимолдаева, Ардак; Бегимбетова , Гульдана (Pedagogy and Psychology, 2023)
Measurement constants of social and psychological health of subjects of education